Altered Posttranslational Modification of Microtubules Contributes to Disturbed Enterocyte Morphology in Celiac Disease - Stricker, Sebastian; Müller, Manuel; Zimmer, Klaus-Peter; Jacob, Ralf; Justus Liebig University Giessen (My University, 2023)
Celiac disease (CD) represents a frequent autoimmune disease triggered by the ingestion of gliadin in genetically predisposed individuals. The alteration of enterocytes and brush border membrane morphology have been repetitively demonstrated, but the underlying mechanisms remain unclear. Microtubules represent a major element of the cytoskeleton and exert multiple functions depending on their tyrosination status. The aim of our study was to investigate whether posttranslational modification of microtubules was altered in the context of CD and whether this mechanism contributed to morphological changes of CD enterocytes. We examined the expression of tubulin tyrosine ligase (TTL) and vasohibin-2 (VASH2) and the level of detyrosinated and acetylated tubulin in duodenal biopsies and Caco-2 cells by immunoblot and immunofluorescence microcopy. Electron microscopy was performed to investigate the subcellular distribution of detyrosinated tubulin and brush border membrane architecture in CD biopsies and Madin–Darby Canine Kidney type II (MDCK) cells lacking TTL. CD enterocytes and Caco-2 cells stimulated with digested gliadin or IFN-y displayed a flattened cell morphology. This disturbed cellular architecture was accompanied by an increased amount of detyrosinated and acetylated tubulin and corresponding high expression of VASH2 and low expression of TTL. The altered posttranslational modification of tubulin was reversible after the introduction of the gluten-free diet. CD enterocytes and MDCK cells deficient in TTL displayed a reduced cell height along with an increased cell width and a reduced number of apical microvilli. Our results provide a functional explanation for the observed morphological alterations of the enterocytes observed in CD and provide diagnostic potential of the tyrosination status of microtubules as an early marker of villous atrophy and CD inflammation.
Keywords: celiac disease; microtubules; detyrosinated tubulin; tubulin tyrosine ligase; vasohibin-2; ddc:610